Levels and risks of particulate-bound PAHs in indoor air influenced by tobacco smoke: a field measurement - Slezakova, Klara (2015)
Considering tobacco smoke as one of the most health-relevant indoor sources, the aim of this work was to further understand its negative impacts on human health. The specific objectives of this work were to evaluate the levels of particulate-bound PAHs in smoking and non-smoking homes and to assess the risks associated with inhalation exposure to these compounds. The developed work concerned the application of the toxicity equivalency factors approach (including the estimation of the lifetime lung cancer risks, WHO) and the methodology established by USEPA (considering three different age categories) to 18 PAHs detected in inhalable (PM10) and fine (PM2.5) particles at two homes. The total concentrations of 18 PAHs (ΣPAHs) was 17.1 and 16.6 ng m−3 in PM10 and PM2.5 at smoking home and 7.60 and 7.16 ng m−3 in PM10 and PM2.5 at non-smoking one. Compounds with five and six rings composed the majority of the particulate PAHs content (i.e., 73 and 78 % of ΣPAHs at the smoking and non-smoking home, respectively). Target carcinogenic risks exceeded USEPA health-based guideline at smoking home for 2 different age categories. Estimated values of lifetime lung cancer risks largely exceeded (68–200 times) the health-based guideline levels at both homes thus demonstrating that long-term exposure to PAHs at the respective levels would eventually cause risk of developing cancer. The high determined values of cancer risks in the absence of smoking were probably caused by contribution of PAHs from outdoor sources.